Cervical cancer vaccination awareness and acceptance among the females of Punjab, Pakistan - Sadia Minhas; Aneequa Sajjad; Muhammad Kashif; Zobaria Rehman; Muhammad Idrees; Farheen Ansari (Makara Journal of Health Research, 2020)
Background: In developing countries like Pakistan, it is essential for health care professionals to have comprehensive knowledge regarding cervical cancer.